Politically Induced Regulatory Risk and Independent Regulatory Agencies - Roland Strausz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
Uncertainty in election outcomes generates politically induced regulatory risk. For monopoly regulation, political partiesŕisk attitudes towards such risk depend on a fluctuation effect that hurts both parties and an output–expansion effect that benefits at least one party. Irrespective of the partiesŕisk attitudes, political parties have incentives to negotiate away regulatory risk by pre-electoral bargaining. Pareto-efficient bargaining outcomes fully eliminate regulatory risk and are attainable through institutionalizing independent regulatory agencies with a specific objective. Key aspects of the regulatory overhaul of the US Postal system in 1970 are argued to be consistent with these results.
Keywords: D82; 330; regulation; independent regulatory agency; regulatory risk; electoral uncertainty